HOTS-AEP OF CLIMATE CHANGE (HOTS-AEPCC) DAN TOPIK BIOTEKNOLOGI UNTUK EKOPEDAGOGIK PADA PEMBELAJARAN IPA - Ilmi Zajuli Ichsan; Ahman Sya; Sunaryo Sunaryo; Achmad Husen; Diana Vivanti Sigit; Yosi Laila Rahmi; Miza Nina Adlini; Titin Titin; Nurfadhilah Nurfadhilah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
Climate change is a phenomenon that discusses in one of the topics of Science (IPA) that could be integrated with biotechnology. The topic might be studied further in terms of ecopedagogy. The purpose of this study was to measure HOTS with the Higher Order Thinking Assessment instrument based on the Environmental Problem of Climate Change (HOTS-AEPCC) and to analyze the relationship between ecopedagogy and biotechnology. The method used in this research was descriptive with the data collection technique using a survey. The results indicated that the students' HOTS scores as measured by HOTS-AEPCC were still in the low category. Therefore, the results of the analysis showed that the topic of biotechnology in science learning was suitable. It assumed that ecopedagogy could combine with biotechnology. This study concludes that the students' HOTS score is still low. Therefore it is necessary to develop science learning oriented to climate change.